How much we know about bisphosphonate lesions - Pešić Zoran; Zarev Miloš; Ranđelović Jovana (Medicinski fakultet i Klinika za stomatologiju, Niš, 2016)
Introduction: Bisphosphonate drugs are used in the treatment of the osteoporosis and malignant processes in the bone tissue. As a result of this use bisphosphonate lesions are formed in bone tissue and oral mucosis, which representing a remarkable therapeutic problem. The aim of this study was to determine how many dentists in general practice are familiar with the character, diagnosis and therapy bisphosphonate lesions. Material and Methods: An anonymous questionnaire of 13 questions was conducted in dental practices in Nis County in the period from October 2015 to December 2015. The obtained data were statistically analyzed. Results: A total of 60% dentists knew what drugs are used in the treatment of osteoporosis and malignant processes in the bones. 25% knew what the bisphosphonate bone lesions are . 66, 6% of dentists knewn what is the prevention of bisphosphonate lesions. 63.3% of dentists are aware of the complications bisphosphonate lesions. Conclusion: Dentists in general practices are insufficiently familiar with the character, diagnosis and treatment of bisphosphonate lesions. We should activate all entities that participate in more continuous medical education, in order to achieve a higher level of prevention of these therapeutic ungrateful lesions.